2015
DOI: 10.1007/s40263-015-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of the Monoamine Oxidase-B Inhibitors for Parkinson’s Disease

Abstract: Inhibitors of monoamine oxidase-B (MAO-B) occupy an important place in the treatment of Parkinson's disease. Selegiline was the first MAO-B to be used therapeutically, while rasagiline is a second-generation drug with higher potency and selectivity. Safinamide is an investigational MAO-B inhibitor with non-dopaminergic properties that may provide advantages over its predecessors. As a class, MAO-B inhibitors are safe and well tolerated and provide symptomatic benefit both as monotherapy and in combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 92 publications
(97 reference statements)
2
44
0
1
Order By: Relevance
“…Robakis and Fahn discussed the role of MAO‐B inhibitors for Parkinson's disease, including selegiline, rasagline and safinamide in their review. In line with the other reviews, they concluded that MAO‐B inhibitors may be useful in the treatment of early and mild Parkinson's disease, and that they do not provide the same antiparkinsonian effect as levodopa . In a post‐hoc analysis, Hauser et al .…”
Section: Discussionmentioning
confidence: 97%
“…Robakis and Fahn discussed the role of MAO‐B inhibitors for Parkinson's disease, including selegiline, rasagline and safinamide in their review. In line with the other reviews, they concluded that MAO‐B inhibitors may be useful in the treatment of early and mild Parkinson's disease, and that they do not provide the same antiparkinsonian effect as levodopa . In a post‐hoc analysis, Hauser et al .…”
Section: Discussionmentioning
confidence: 97%
“…Both MAO-A and MAO-B are being discussed to provide beneficial, neuroprotective effects for PD patients (Naoi, Maruyama, Inaba-Hasegawa, & Akao, 2011;Robakis & Fahn, 2015;Kong et al, 2015). It has been demonstrated that MAO-A mediates the increased expression of genes for antiapoptotic, pro-survival Bcl-2, a subgroup of the Bcl-2 family of proteins regulating apoptosis, whereas MAO-B does not.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…L-dihydroxyphenylalanine (L-dopa), a dopamine precursor, is a gold standard for the treatment of PD, but it has only a limited success in improving motor impairments and after some years the effect declines and patients may start to suffer from severe dyskinesias. [1][2] Recently, selegiline and rasagiline, the two selective and irreversible monoamino oxidase (MAO) inhibitors have been approved by the US FDA for the treatment of PD. It has been suggested that, these inhibitors may have neuroprotective effect and play as disease-modifying agent role in PD.…”
Section: Introductionmentioning
confidence: 99%
“…However, in compared to levodopa and dopamine agonists, MAO inhibitors at best, have the modest effect on the symptomatic relief of PD. 2 Therefore, new targets for potential pharmacological intervention should be explored and evaluated in order to slow down, delay or reverse the progress of this disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation